Combining an ongoing panel with a new cross-sectional sample - Martin Spiess; Ulrich Rendtel (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
In this paper, a weight is derived for the calculation of design based estimators of totals, means and proportions using the ongoing German Socio-Economic Panel (GSOEP) and a new cross-sectional sample. In the first part of the paper, the selection schemes of the subsamples A, B, C and D of the ongoing panel and of the new sample (sample E) are described. Using some similarity assumptions and starting from a general formulation, an optimal weight in the sense of small variances of design-based estimators using both samples is derived. The merits of this approach as well as some disadvantages are discussed.
Keywords: 330; design based inference; convex weighting estimator; complex surveys; panel survey; cross-sectional sample; Mikroökonometrie; Panel; Stichprobenverfahren; Aggregation; Theorie; Deutschland; GSOEP